A Study of Basal Cell Carcinoma in South Asians for Risk Factor and Clinicopathological Characterization: A Hospital Based Study. (3rd November 2014) - Kumar, Sumir; Mahajan, Bharat Bhushan; Kaur, Sandeep; Yadav, Ashish; Singh, Navtej; Singh, Amarbir
Abstract : Objectives . Although the incidence of skin cancers in India (part of South Asia) is low, the absolute number of cases may be significant due to large population. The existing literature on BCC in India is scant. So, this study was done focusing on its epidemiology, risk factors, and clinicopathological aspects. Methods . A hospital based cross-sectional study was conducted in Punjab, North India, from 2011 to 2013. History, examination and histopathological confirmation were done in all the patients visiting skin department with suspected lesions. Results . Out of 36 confirmed cases, 63.9% were females with mean ± SD age being 60.9 ± 14.2 years. Mean duration of disease was 4.7 years. Though there was statistically significant higher sun exposure in males compared to females (P value being 0.000), BCC was commoner in females, explainable by intermittent sun exposure (during household work in the open kitchens) in women. Majority of patients (88.9%) had a single lesion. Head and neck region was involved in 97.2% of cases, with nose being the commonest site (50%) with nodular/noduloulcerative morphology in 77.8% of cases. Pigmentation was evident in 22.2% of cases clinically. Nodular variety was the commonest histopathological variant (77.8%). Conclusions . This study highlights a paradoxically increasing trend of BCC with female preponderance, preferential involvement of nose, and higher percentage of pigmentation in Indians.